Otomasi Kandang Dalam Rangka Meminimalisir Heat Stress Pada Ayam Broiler Dengan Metode Naive Bayes - Chandra Gusti Nanda Putra; Rizal Maulana; Hurriyatul Fitriyah (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The temperature rise exceeds the comfort zone resulting in heat sress in chickens, where broiler chickens will experience a decline in growth, decreased feeding, anxiety, increased water consumption and resulted in death. Broiler chicken comfort zone temperature ranges between 20-25 Â° C and humidity range 50-70%, whereas the problems of current temperature fluctuating between indonesia's 29-36 Â° C. Based on the issue of his automation system to minimize heat stress. This research uses 2 parameters, namely the temperature and moisture sensor readings from the DHT11 as the input and output speed fan and close the curtains open on the system. To specify output fan and curtain using a calculation method klasfikasi method of naive bayes. It can be concluded that the system is able to minimize heat stress with testing done for 2 weeks using the 600 broiler chickens where the death of a chicken before using the automation system that is amounted to 64 and after using the automation system is 31 tail.